Adoption of sustainable agricultural practices among smallholder dairy farmers in Malaysia: Contributing factors and smart farming prospects / Thanuja Rathakrishnan ... [et.al.]. - Rathakrishnan, Thanuja; Suntharalingam, Chubashini; Shern, Lim Yi; Keng, Loong Shih; Lee Hai, Yen; Kok, Tee Keng; Thanarajoo, Sathis Sri; Balasundram, Siva K (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Adoption of Sustainable Agricultural Practices (SAP) among smallholder dairy farmers in developing countries, especially within the Asia Pacific region remains low. This is probably attributable to the fact that psycho-social factors are not considered during the adoption process. The current study was carried out in order to increase the adoption of SAP in Malaysia, by investigating psycho-social factors among dairy farmers. It adopted the enhanced Theory of Planned Behaviour to investigate smallholder dairy farmers’ intention to uptake SAP in Malaysia. This study applied the Partial Least Squares Structural Equation Modelling (PLS-SEM) to model how psycho-social factors influence farmers’ SAP adoption decisions.